Education and Technology - Rossella Marzullo (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The aim of this paper is to explore what we know about the difficulties from comprehension of digital texts in comparison with traditional texts with a particular focus on new readers. The question we want to investigate is whether the reading of an electronic text is more (or less) difficult than that of a paper text. In the first part of the paper, the object of the study is presented; in the second part research studies in the field are examined through an analysis of the evidence-based literature; in the third and final part, we try to draw some conclusions from data. Do we read more or read less in the time of digital media? Does reading on the screen change the way we understand meanings? And does the way we write change? These are some of the questions that parents and teachers ask themselves to understand what are the correct spaces and times to leave for devices at home, at school, in free time. Research suggests that the question of time is crucial. Maryanne Wolf, a neuroscientist who has been studying the brain that reads for years, noted that reading on the screen ends up inhibiting deep reading in the long run. We run away, looking for some articulations of the text that allow us to synthetically grasp its meaning without taking the time to weigh every single part: the risk is that the ability to understand exactly the meaning of what is being read is compromised. Fast thoughts and slow thoughts should both belong to our cognitive economy: the former are useful in some cases, the latter in others. In fact, however, the speed at which we are progressively more and more required in everyday life, at home as well as in organizations, can mean that we tend to resort more and more frequently, especially to quick thoughts. The real problem, therefore, is not digital, but speed. We need to find a way to slow down because only by slowing down is it possible to activate our slow thoughts.